Atensi, Koneksi-Diskoneksi, dan Hal-Hal yang Mempersulitnya - Bawono, Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2024)
Book & Film Reviews is a column in "MELINTAS" containing reviews of books and films published recently that bring different interpretation and inspiration to the fields of philosophy and religion.